Hypoglycemia Incidence Among Patients With Type 2 Diabetes Mellitus Receiving Antidiabetic Therapy: A Retrospective Hospital-Based Study in South Kalimantan, Indonesia - Nadiyah Wafa; Tyas Setia Nugraha; Herda Ariyani (International Journal of Health and Pharmaceutical (IJHP), 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease with an increasing prevalence. Antidiabetic drugs (OAD) are necessary for glycemic control, but they carry the risk of causing hypoglycemia. Objective: This study aimed to assess patient characteristics, OAD usage patterns including drug type, dosage, and regimen, hypoglycemic complaints, and side effect categories using the Naranjo Algorithm. Method: A descriptive, observational quantitative study with a retrospective, non-experimental design was conducted at Brigjend H. Hasan Basry Regional General Hospital (RSUD) Kandangan, utilizing medical record data and interviews. Samples were taken via total sampling from T2DM patients with hypoglycemia in 2025, followed by univariate analysis. Results: Of the 18 patients, 11 met the criteria, but only 7 underwent further analysis. The majority of patients who experienced hypoglycemia were over 60 years of age (85.7%) and female (85.7%), with hypertension being the most common comorbidity (57.1%). The pattern of oral antidiabetic (OAD) use was dominated by sulfonylurea monotherapy, specifically glimepiride at a dose of 2 mg once daily (42.8%). The most frequently reported primary complaint was weakness. Based on the Naranjo algorithm, most hypoglycemia cases fell into the Probable category (85.7%), while 14.3% fell into the Possible category. Conclusion: Type 2 diabetes patients with risk factors such as advanced age, female gender, comorbid hypertension, and the use of glimepiride constitute the group at highest risk for hypoglycemic events. Findings regarding incomplete data and misconceptions about medication instructions indicate a need for optimized patient and family education, as well as comprehensive therapy monitoring.